A retrospective analysis of systemic Norepinephrine impact on tangential excision and split thickness skin graft outcomes in burn shock patients - Albin John; Ilina Terziyski; Annie Snitman; John Garza; Alan Pang; Callie Adams; Grant Sorensen; John Griswold (Elsevier, 2023)
Objective: Burn shock is a serious complication that presents with profound cardiovascular suppression that may require vasopressor support for hemodynamic stability. This study aims to explore the patterns of systemic Norepinephrine use and skin graft take in patients with deep burns requiring excision and grafting. Methods: Burn patients ages 18-89 years that presented to our regional burn center from January 2014-June 2020 and were treated with systemic vasopressors within the first 48 h of admission, and received at least one tangential excision and split thickness skin graft (STSG) procedure as part of their treatment were retrospectively identified. Patients receiving vasopressors were compared to a matched cohort of patients not receiving vasopressors yet with similar demographics, burn trauma, and smoke inhalation injury. Major outcomes investigated included: average overall graft take, amount of Norepinephrine received, total amount of fluids used for resuscitation, number of operations, and length of hospital stay. Results: The mean graft uptake for patients treated with systemic Norepinephrine (80.0%) was significantly lower than the mean graft uptake for patients not treated with systemic Norepinephrine (91.4%, p < 0.001). Conclusion: Patients with burn shock should be primarily managed with fluid resuscitation with addition of vasopressors only if absolutely necessary.